The Iconographic Program of the Mosaics from the Roman villa of “El Alcaparral” (Casariche, Seville) in the conventus Astigitanus - Neira Jiménez, Luz (Gerión. Revista de Historia Antigua, 2021)
This work deals with the analysis of the iconographic program of the mosaics that paved the main building of the villa of “El Alcaparral” (Casariche, Seville). They are 15 pavements discovered in the archaeological excavations performed in the site in 1985 and 1986. Among the mosaics discussed, the mosaic of Paris, the fragmentary mosaic of the marine thiasos with nereids, a mosaic with an allegorical depiction and pavements with geometric schemes, some of the which are preserved in the Casariche Museum Colection. Based on the original archaeological reports, plan and photographs, recorded 30 years ago, the analysis of the program follows the same course of the preserved rooms, from the entrance, contributing to study of each mosaic the parallels discovered in the last years- in order to obtain not only a full picture of the mosaic program but also of the architectural context of the villa “El Alcaparral” and the mentality of its dominus.
Keywords: Villae; Roman Mosaics; Judgement of Paris; Nereids; Allegoric Personification; Geometric Schemes